ΠΟΛΙΤΙΚΕΣ ΤΕΛΕΤΟΥΡΓΙΕΣ ΣΤΗ ΝΕΩΤΕΡΗ ΕΛΛΑΔΑ. Η ΜΕΤΑΚΟΜΙΔΗ ΤΩΝ ΟΣΤΩΝ TOΥ ΓΡΗΓΟΡΙΟΥ Ε’ ΚΑΙ Η ΠΕΝΤΗΚΟΝΤΑΕΤΗΡΙΔΑ ΤΗΣ ΕΛΛΗΝΙΚΗΣ ΕΠΑΝΑΣΤΑΣΗΣ - ΕΞΕΡΤΖΟΓΛΟΥ ΧΑΡΗΣ (Μνήμων, 2001)
Haris Exertzoglou, Political rituals in Modem Greece: the reburial ofPatriarch Gregory V and the 50th anniversary of the Greek Revolution This paper explores political rituals in Modern Greece by focusing onthe 50th anniversary of the start of Greek War of Independence andthe particular place of a reburial procession in the celebrations. In 1871 the Greek state decided to proceed with the rehurial of Patriarch GregoryV, whose body, allegedly found a few days after his execution bythe Ottomans in 1821, was buried in Odessa. The decision was not simplya gesture of respect; it was meant to support the 50th anniversary ofthe Greek Revolution, and the reburial procession was planned as themain event of the celebration. As such, the reburial of Gregory V wasused as a means of making the heroic meaning of the Revolution visible,to attract mass attention and mobilize the participation of thepublic. Admittedly, the anniversary proved a major success. However,the reburial procession, the key event of the celebration, exposed atension in the celebration: not only the mourning dimension of theprocession was not compatible with the gay aspects of the nationalfeast, it also generated varied meanings, some of them directly opposingthe heroic memory of the Revolution and the irredentist prospects ofthe Greek state. This aspect suggests that, however successful, politicalrituals are inherently contradictory events always susceptible to various,even contingent, uses.